PROSES PEMBUATAN MOBIL PORSCHE 356 A COUPE DALAM FOTOGRAFI STORY - Putra, I Kadek Aldi Margareta Perdana; Suardana, I Wayan; Raharjo, Anis (Retina Jurnal Fotografi, 2023)
The purpose of the Internship/Work Practice is to show how to capture a classic car by presenting a different visualization. Data were collected by observation, interview, and documentation methods. The results as long as the authors carry out the MBKM Internship/Work Practice program at Tuksedo Studio, the authors get new technologies such as tools and software used when working on projects provided by partners. The new technology in the form of tools used is the Blackmagic Pocket Cinema Camera 4K and the Zhiyun CRANE 3 Lab Handheld Stabilizer. In making Photo Story, the author uses the EDFAT method, Photography Composition technique, and digital processing that the author learned while in college.